Analytics of the Technology Transfer Cost Issue (The Pakistan Development Review, 1976)
An increasingly important issue of trade and development is the high cost of the transfer of technology from the developed countries to the develop¬ing world. Rough estimates suggest that payments by developing countries for the use of patents, licenses, trademarks, and managerial and technical services amounted to about SI.5 billion in 1968 [19]. For Pakistan, the issue is of particular importance.1 Based on conservative estimates by Mahbub ul Haq, Pakistan's annual payments for technology transfer in 1965-70 averaged $102 million; this magnitude—again reflecting payments for the use of patented knowledge and technical services only—represents a payment rate of almost 16 percent of annual export receipts [19]. If other costs such as profit repatria¬tion and transfer pricing are included, the payment rate is substantially higher.